2002
DOI: 10.1038/sj.bmt.1703641
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of HLA-identical sibling and voluntary unrelated allogeneic bone marrow and peripheral blood stem cell transplantation in adults with acute myelocytic leukaemia or acute lymphoblastic leukaemia

Abstract: Summary:Allogeneic stem cell transplantation (SCT) is one of the most expensive medical procedures. However, only a few studies to date have addressed the costs of HLAidentical sibling transplantation and only one study has reported costs of unrelated transplantation. No recent cost analysis with a proper follow-up period and donor identification expenses is available on related or voluntary matched unrelated donor (MUD) SCT for adult AML or ALL. Therefore, we calculated direct medical (hospital) costs based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 14 publications
1
39
0
Order By: Relevance
“…6 The reported costs varied greatly, from US$ 60,000 to 200,000. 9,11 This difference in costs may be explained by differences in methodologies, inclusion periods, countries, populations, health coverage policies and graft type. In 2002, van Agthoven 11 reported that, for patients with acute leukemia, the cost over a period of 2 years, including the donor search, was € 151,754 per patient and increased to €173,587 for patients still alive 2 years after transplantation.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The reported costs varied greatly, from US$ 60,000 to 200,000. 9,11 This difference in costs may be explained by differences in methodologies, inclusion periods, countries, populations, health coverage policies and graft type. In 2002, van Agthoven 11 reported that, for patients with acute leukemia, the cost over a period of 2 years, including the donor search, was € 151,754 per patient and increased to €173,587 for patients still alive 2 years after transplantation.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…In the first published studies, the estimated costs for HSCT varied greatly (Online Supplementary Table S1) depending on the country in which they were performed, type of donor, transplant center procedures and year of transplantation. 5,7,[9][10][11] A more recent comparative study of autologous and allogeneic HSCT for patients transplanted for hematologic malignancies in the USA estimated a 100-day total cost of US$ 203,026 for allogeneic HSCT. 12 Unrelated donor cord blood transplantation (UCBT) has become a widely accepted transplant modality in the absence of an HLA-matched donor.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by Van Agthoven et al 25 in the Netherlands, the average cost for allogeneic transplantation was h103 509 (inclusive of donor identification expenses) in a case series (N ¼ 47) that included only patients alive after 2 years of follow-up.…”
Section: Cost Assessmentsmentioning
confidence: 99%
“…After inspection of each of these studies, four papers [23][24][25][26] were found to be pertinent for our analysis. As regards allogeneic SCT, Mishra et al 23 estimated the cost incurred by 17 patients in Norway; these authors analysed pre-transplant procedures, transplantation and 1-year follow-up costs; sources of cost included harvesting, personnel costs, clinical and laboratory procedures, along with blood products and drugs related to patients and donors.…”
Section: Cost Assessmentsmentioning
confidence: 99%
“…In using this estimate the same assumptions were made about the appropriateness of the original source of the costs. 203 It was additionally assumed that, unlike the cost of the procedure, long-term costs are independent of type of transplantation and age of patient at the time of transplantation.…”
Section: Administration and Monitoring Costsmentioning
confidence: 99%